Inhibition efficiency of wood vinegar on grey mould of table grapes. (December 2020) - Chen, Yu-Hang; Li, Yi-Fan; Wei, Huan; Li, Xiao-Xia; Zheng, Huai-Tang; Dong, Xin-Yi; Xu, Teng-Fei; Meng, Jiang-Fei
Abstract: Botrytis cinerea can cause grey mould and seriously affect the commercial value of grapes. An artificial inoculation trial was done using table grape 'Red Globe' ( Vitis vinifera L.). Grape berries were treated either with ultrapure water or 600, 400, 200 times dilution of wood vinegar (WV), followed by inoculation with B. cinerea suspension after 24 h. Disease incidence (DI), disease severity (DS), malondialdehyde (MDA) and hydrogen peroxide content and activities of peroxidase, ascorbate peroxidase, superoxide dismutase, polyphenol oxidase, chitinase, and β-1, 3-glucanase were determined every two days during B. cinerea infection. Compared with the positive control group, WV treatment significantly reduced the DI and DS of grapes infected with grey mould. WV significantly decreased the amount of hydrogen peroxide and MDA and promoted the accumulation and expression of antioxidant enzyme in grapes. These results suggested the efficacy of WV treatment in improving the resistance of 'Red Globe' grapes to grey mould and in mitigating harm caused by oxidative stress.